MENDETEKSI KECURANGAN LAPORAN KEUANGAN DENGAN MENGGUNAKAN TEORI FRAUD PENTAGON : MENDETEKSI KECURANGAN LAPORAN KEUANGAN DENGAN MENGGUNAKAN TEORI FRAUD PENTAGON - Dhiya Auliani; Eha Nugraha; Ermina Sari (Jurnal Inovasi, Keuangan, Manajemen dan Akuntansi, 2025)
Many companies conceal their actual financial condition through manipulation of financial statements. To prevent such fraud, effective detection methods are essential one of which is the fraud pentagon model. This study investigates how components of the fraud pentagon can help detect potential financial statement fraud, based on agency theory and fraud pentagon theory. This quantitative study relies on secondary data from annual reports. The proxies analyzed include external pressure, ineffective monitoring, total accrual ratio, director changes, and the frequency of CEO photographs, covering the period from 2018 to 2022. Using purposive sampling, the study applies classical assumption testing and multiple linear regression for hypothesis testing. The sample consists of 18 food and beverage companies listed on the Indonesia Stock Exchange, totaling 90 observations. Findings reveal that external pressure and change of director have a partially significant influence on the likelihood of financial statement fraud. Meanwhile, ineffective monitoring, total accrual ratio, and frequent CEO photo appearances show no significant partial effect.